Virtual item trade scams: A typology of young victims - Kristiansen, Søren (International review of victimology, 2025)
This study examined behavioral differences across groups of children and young people who have been victims of virtual item trade scams to explore the potential for grouping this type of victims into meaningful clusters. Using data from a representative survey among Danish children and young people (n = 1,026), three clusters of trade scam victims that showed significant internal homogeneity as well as cross-cluster differences were identified. Based on their modal behavior, these clusters were labeled Moderately Engaged Gamers, Diverse Active Gamers, and Highly Engaged Gamers. The typology represents a first step toward a better understanding of different types of virtual item trade scam victims and their behavioral patterns. Implications for policy and preventive measures on game design, personal, and parental levels are discussed.